Политическое управление развитием Арктики (Анализ основных этапов становления) - Kosov, Yuri V.; Nikolaenko, Anastasiya Valentinovna (Administrative consulting, 2025)
The Arctic is the geostrategic, geopolitical region in which the national and state interests of the Russian Federation are formed at present. The questions connected with a control system of the Arctic region of the Russian Federation in a historical retrospective and at the present are considered in article and also the main features of modern process of management of the Arctic are analyzed.